Against All Common Sense. The Mediatized Legend of Juve Caserta between Basketball Epics, Aged Sports Celebrities, and Collective Memory in the Docu-Series Scugnizzi per sempre. - Mario Tirino (Funes)
This article investigates the TV docu-series Scugnizzi per sempre (2023) as an example of narrative mediatization of sports. Using narrative analysis and media content analysis applied to television seriality, the article aims to focus on three essential elements: 1) the identification of the thematic cores that develop the celebration of the epic feat of the Juve Caserta basketball club; 2) the ways through which the RAI docu-series (re)connects fandom with the aged sports celebrities and the collective memory of the Scudetto victory (1991); 3) the analysis of storylines and sequences through which the docu-series elaborates a kind of reflexive mediatization (or meta-mediatization), recounting the role of news media and communication technologies within the series’ storytelling.